Apoptotic mechanisms of gastric cancer cells induced by isolated erinacine S through epigenetic histone H3 methylation of FasL and TRAIL. Issue 8 (29th March 2021) - Tung, Shui-Yi; Lee, Ko-Chao; Lee, Kam-Fai; Yang, Ya-Ling; Huang, Wen-Shih; Lee, Li-Ya; Chen, Wan-Ping; Chen, Chin-Chu; Teng, Chih-Chuan; Shen, Chien-Heng; Hsieh, Meng-Chiao; Huang, Cheng-Yi; et al.
Abstract : Erinacine S, the new bioactive diterpenoid compound isolated from the ethanol extract of the mycelia of Hericium erinaceus, displays great health-promoting properties. Abstract : Erinacine S, the new bioactive diterpenoid compound isolated from the ethanol extract of the mycelia of Hericium erinaceus, displays great health-promoting properties. However, the effects of erinacine S on inductive apoptosis in cancer cells such as gastric cancer and its molecular mechanisms remain unclear. Our results demonstrated that erinacine S treatment significantly induces cell apoptosis with increased ROS production in gastric cancer cells, but not in normal cells. Significantly, erinacine S also showed its inhibitory effects on tumor growth in an in vivo xenograft mouse model. Furthermore, immunohistochemical analyses revealed that erinacine S treatment significantly increases the FasL and TRAIL protein, whereas it decreases the levels of PCNA and cyclin D1 in the gastric cancer xenograft mice. Consistently, in AGS cells, erinacine S treatment not only triggers the activation of extrinsic apoptosis pathways (TRAIL, Fas-L and caspase-8, -9, -3), but it also suppresses the expression of the anti-apoptotic molecules Bcl-2 and Bcl-XL in a time-dependent manner. In addition, erinacine S also causes cell cycle G1 arrest by the inactivation of CDKs/cyclins. Moreover, our data revealed that activation of the ROS-derived and AKT/FAK/PAK1 pathways is involved in the erinacine S-mediated transcriptional activation of Fas-L and TRAIL through H3K4 trimethylation on their promoters. Together, this study sheds light on the anticancer effects of erinacine S on gastric cancer and its molecular mechanism in vitro and in vivo .